A Case With Pyruvate Kinase Deficiency Remarkably Sensitive to Heat. Issue 7 (October 2018) - Aksu, Tekin; Yarali, Neşe; Fermo, Elisa; Marcello, Anna; Hacisalihoğlu, Şadan; Bianchi, Paola; Özbek, Namik Y.
Abstract : Pyruvate kinase (PK) deficiency is the most common defect of the glycolytic pathway leading to congenital hemolytic anemia. We present the case of an 18-year-old boy with chronic nonspherocytic hemolytic anemia, who had remarkable sensitivity to heat. Moreover, the patient showed clinical impairment in the last year. For this reason, we excluded the immunologic or infectious nature (malaria, babesia), which may play a role in the worsening of anemia. Red blood cell enzyme assay showed the presence of a significant increase in other enzyme activities, except for PK, suggesting a PK deficiency in the patient. The molecular analysis of the PK-LR gene revealed the presence of a novel homozygote missense mutation (c.581G>C, p.Arg194Pro). The mutant enzyme displayed heat instability. In addition, we analyzed bilirubin uridine diphosphate (UDP)-glucuronosyltransferase 1A1 gene that revealed a heterozygous state ([TA]6/[TA]7). After a clear diagnosis of PK deficiency, the patient underwent splenectomy.